Deep level effects on the characteristics of high electron mobility transistors grown by solid source MBE - Yip, Kim Hong. (2008)
This thesis presents the effect of deep levels on the performance of InxGa1-xP/In0.20Ga0.80As/GaAs and AlyGa1-yAs/In0.20Ga0.80As/GaAs pseudomorphic high electron mobility transistor (pHEMT) grown by solid source molecular beam epitaxy (SSMBE).